EFFECT OF RESVERATROL ON BLOOD PRESSURE: A SYSTEMATIC REVIEW AND META-ANALYSIS OF RANDOMIZED, CONTROLLED, CLINICAL TRIALS. (June 2018) - Fogacci, F.; Cicero, A.F.G.; Tocci, G.; Presta, V.; Fratter, A.; Borghi, C.
Abstract: Objective: We aimed to assess the impact of resveratrol on BP through systematic review of literature and meta-analysis of available randomized, controlled clinical trials (RCTs). Design and method: Literature search included SCOPUS, PubMed-Medline, ISI Web of Science and Google Scholar databases up to 17th October 2017 to identify RCTs investigating the impact of resveratrol on BP. Two review authors independently extracted data on study characteristics, methods and outcomes. Overall, the impact of resveratrol on BP was reported in 17 trials. Results: Administration of resveratrol did not significantly affect neither systolic BP [weighted mean difference (WMD): −2.5 95%CI:(−5.5, 0.6) mmHg; p = 0.116; I2 = 62.1%], nor diastolic BP [WMD: −0.5 95%CI:(−2.2, 1.3) mmHg; p = 0.613; I2 = 50.8], nor mean BP [MAP; WMD: −1.3 95%CI:(−2.8, 0.1) mmHg; p = 0.070; I2 = 39.5%] nor pulse pressure [PP; WMD: −0.9 95%CI:(−3.1, 1.4) mmHg; p = 0.449; I2 = 19.2%]. However, significant WMDs were detected in subsets of studies categorized according to high resveratrol daily dosage (more than 300 mg/day) and presence of diabetes. Meta-regression analysis revealed a positive association between systolic BP-lowering resveratrol activity (slope: 1.99; 95%CI: 0.05, 3.93; two-tailed p = 0.04) and Body Mass Index (BMI) at baseline, while no association was detected neither between baseline BMI and MAP-lowering resveratrol activity (slope: 1.35; 95%CI: −0.22, 2.91; twotailed p = 0.09) nor between baseline BMI and PP-lowering resveratrol activity (slope: 1.03; 95%CI: −1.33, 3.39; two-tailed p = 0.39). Resveratrol was fairly well-tolerated and no serious adverse events occurred among most of the eligible trials. Conclusions: The favourable effect of resveratrol emerging from the current meta-analysis suggests the possible use of this nutraceutical as active compound in order to promote cardiovascular health, mostly when used in high daily dose (over 300 mg/day) and in diabetic patients.